Pelvic Inflammatory Diseases- An Ayurvedic Perspective. (International Journal of Ayurveda and Pharma Research, 2022)
Pelvic Inflammatory Disease (PID) is responsible for a considerable disease burden and represents an important healthcare issue in worldwide. PID is the clinical syndrome associated with upper genital tract infection and inflammation caused by the spread of micro-organisms from the lower to upper genital tract. Prevention of PID and recurrent PID is also a public health priority in the present scenario. Clinical signs and symptoms are relayed by clinician to diagnose PID, mainly due to the lack of a minimally or non-invasive diagnostic test that reliably identifies women with upper genital tract inflammation. Aim and objectives: The search for an Ayurveda equivalent of PID in Ayurveda classics doesn’t yield any one disease entity that entirely matches the clinical picture of this condition. Material and Methods: Diagnosis of PID is based on centers for disease control and prevention 2015 PID guideline. Considering it as ‘Anukta Vyadhi’ (unexplained disorder), this review attempts to understand the disorder by deriving its Vikaraprakriti (nature of disease), Adhishtanantarani (structures and sites affected), and Samutthanavishesha (specific etiological factor) based on a detailed analysis of the clinical features and other findings regarding the disease available in various textbooks and articles in the light of related references in Ayurvedic classics. Discussion and conclusion: PIDs are established in terms of Nidana Panchaka (five components of understanding a disease). Pittala and Paripluta Yonivyapad can be implied as pelvic inflammatory diseases